Dissecting the treatment-naive ecosystem of human melanoma brain metastasis - Biermann, Jana; Melms, Johannes C.; Amin, Amit Dipak; Wang, Yiping; Caprio, Lindsay A.; Karz, Alcida; Tagore, Somnath; Barrera, Irving; Ibarra-Arellano, Miguel A.; Andreatta, Massimo; Fullerton, Benjamin T.; Gretarsson, Kristjan H.; et al. (Cell, 2022)
Melanoma brain metastasis (MBM) frequently occurs in patients with advanced melanoma; yet, our understanding of the underlying salient biology is rudimentary. Here, we performed single-cell/nucleus RNA-seq in 22 treatment-naive MBMs and 10 extracranial melanoma metastases (ECMs) and matched spatial single-cell transcriptomics and T cell receptor (TCR)-seq. Cancer cells from MBMs were more chromosomally unstable, adopted a neuronal-like cell state, and enriched for spatially variably expressed metabolic pathways. Key observations were validated in independent patient cohorts, patient-derived MBM/ECM xenograft models, RNA/ATAC-seq, proteomics, and multiplexed imaging. Integrated spatial analyses revealed distinct geography of putative cancer immune evasion and evidence for more abundant intra-tumoral B to plasma cell differentiation in lymphoid aggregates in MBM. MBM harbored larger fractions of monocyte-derived macrophages and dysfunctional TOX+CD8+ T cells with distinct expression of immune checkpoints. This work provides comprehensive insights into MBM biology and serves as a foundational resource for further discovery and therapeutic exploration.